1984
DOI: 10.1177/106002808401801006
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen Toxicity Associated with Declining Renal Clearance after Ibuprofen

Abstract: A 64-year-old male with an incomplete spinal cord injury had been taking baclofen 20 mg tid for 2 1/2 months without side effects. His blood urea nitrogen and serum creatinine rose from 13 and 0.9 mg%, respectively, to 59 and 2.8 mg% after ibuprofen 600 mg tid was begun. The patient displayed baclofen toxicity, developing confusion, disorientation, bradycardia, and hypothermia. His blood pressure dropped and he complained of blurred vision. Ibuprofen discontinuation and fluid repletion corrected the renal indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Reports have also suggested that if ibuprofen drug therapy is initiated, and the patient develops signs of drug toxicity, this may be a sign of ibuprofen-induced renal insufficiency, which further lowers drug clearance. 53 On the other hand, drugs such as gentamicin do not produce an elevated elimination half-life and may be administered with standardized dosing intervals, taking into consideration alterations in the other PK criteria.…”
Section: Pharmacokinetic Alterations In Spinal Cord Injury H Mestre Ementioning
confidence: 99%
“…Reports have also suggested that if ibuprofen drug therapy is initiated, and the patient develops signs of drug toxicity, this may be a sign of ibuprofen-induced renal insufficiency, which further lowers drug clearance. 53 On the other hand, drugs such as gentamicin do not produce an elevated elimination half-life and may be administered with standardized dosing intervals, taking into consideration alterations in the other PK criteria.…”
Section: Pharmacokinetic Alterations In Spinal Cord Injury H Mestre Ementioning
confidence: 99%
“…A similar case of baclofen-induced encephalopathy linked to concurrent use with ibuprofen was reported in the literature. In the case mentioned above, an associated acute kidney injury may have increased the risk of toxicity [ 15 ]. The evidence supporting a direct adverse drug interaction between NSAIDs and baclofen in the absence of impaired renal function is not clearly substantiated.…”
Section: Discussionmentioning
confidence: 99%
“…Medications that affect renal function can also potentiate baclofen toxicity. Therefore, clinicians should be vigilant in identifying the potential risk of renal dysfunction when prescribing baclofen [ 13 ].…”
Section: Discussionmentioning
confidence: 99%